Sb doped ZnO nanostructures prepared via co-precipitation approach for the enhancement of MB dye degradation. (28th February 2018) - Jagadhesan, S; Senthilkumar, N; Senthilnathan, V; Senthil, T S
Abstract: In the present work, simple co-precipitation approach for pure zinc oxide (ZnO) nanoparticles (NPs) and antimony (Sb) doped ZnO Nanostructures (NSs) has been investigated. The phase purity and various functional groups observed from the synthesized materials were confirmed by powder x-ray diffraction (PXRD) and Fourier Transform Infrared Spectroscopy (FTIR) studies. The surface morphology of the spherical like pure ZnO and cubic, hexagonal and net-like Sb (0.05%, 0.075%) doped ZnO NSs are observed by using Field Emission Scanning Electron Microscopy (FESEM) analysis and compositional elements which are presence in the synthesized particles were determined by Energy Dispersive x-ray spectroscopy (EDAX) analysis. The synthesized Sb (0.05% and 0.075%) doped with ZnO NSs acts as the catalyst for photocatalytic activity.